2022
DOI: 10.3390/s22207964
|View full text |Cite
|
Sign up to set email alerts
|

Wrapper Functions for Integrating Mathematical Models into Digital Twin Event Processing

Abstract: Analog sensors often require complex mathematical models for data analysis. Digital twins (DTs) provide platforms to display sensor data in real time but still lack generic solutions regarding how mathematical models and algorithms can be integrated. Based on previous tests for monitoring and predicting banana fruit quality along the cool chain, we demonstrate how a system of multiple models can be converted into a DT. Our new approach provides a set of generic “wrapper functions”, which largely simplify model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The simulations for Kriging and Margolis showed that single-delay resampling is feasible. Data from wireless sensors can be integrated with subsequent processing, e.g., by digital twins [4], even if the sensor timing is distorted by jitter or missing samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulations for Kriging and Margolis showed that single-delay resampling is feasible. Data from wireless sensors can be integrated with subsequent processing, e.g., by digital twins [4], even if the sensor timing is distorted by jitter or missing samples.…”
Section: Discussionmentioning
confidence: 99%
“…This can be illustrated by an example application from our previous research on remote container monitoring. Wireless sensors were mounted inside a reefer container with bananas [4]. Data were transmitted over local and global networks to a server.…”
Section: Example Application and Outlinementioning
confidence: 99%